An electron microscopy study of b-FeOOH (akaganeite) nanorods and nanotubes - Richmond, William; Cowley, J.; Parkinson, Gordon; Saunders, M. (The Royal Society of Chemistry, 2006)
High-resolution TEM images reveal that samples of b-FeOOH (akaganeite) prepared by quenching of a condensed ferrihydrite gel contain a mixture of rod-like particles and tubes. The tubular particles are usually about 10-15 nm in diameter with a central void that is typically 1/3 of the particle diameter. Dark-field STEM images show that the tubular particles are made up of single crystals that extend across the whole tube diameter, but only rarely extend along the whole length of the tube. Both the solid rods and the tubes appear to be based on subunits of approximately 3-4 nm in diameter, and it is proposed that formation of the akaganeite particles, both tubes and rods, results from secondary nucleation of these subunits at sites on particle edges, followed by rapid linear growth along the c-direction of the akaganeite structure.